Macrophage – tumor cell interaction beyond cytokines - Kovaleva, Olga; Sorokin, Maxim; Egorova, Anastasija; Petrenko, Anatoly; Shelekhova, Ksenya; Gratchev, Alexei (Frontiers in Oncology, 2023)
Tumor cells communication with tumor associated macrophages is a highly important factor of tumor malignant potential development. For a long time, studies of this interaction were focused on a cytokine- and other soluble factors -mediated processes. Discovery of exosomes and regulatory RNAs as their cargo opened a broad field of research. Non-coding RNAs (ncRNAs) were demonstrated to contribute significantly to the development of macrophage phenotype, not only by regulating expression of certain genes, but also by providing for feedback loops of macrophage activation. Being a usual cargo of macrophage- or tumor cell-derived exosomes ncRNAs provide an important mechanism of tumor-stromal cell interaction that contributes significantly to the pathogenesis of various types of tumors. Despite the volume of ongoing research there are still many gaps that must be filled before the practical use of ncRNAs will be possible. In this review we discuss the role of regulatory RNAs in the development of macrophage phenotype. Further we review recent studies supporting the hypothesis that macrophages may affect the properties of tumor cells and vice versa tumor cells influence macrophage phenotype by miRNA and lncRNA transported between these cells by exosomes. We suggest that this mechanism of tumor cell – macrophage interaction is highly promising for the development of novel diagnostic and therapeutic strategies, though many problems are still to be solved.